Universal Design in Interior Architecture Education: The Case of Store Design - Sariye Selhan Yalçın Usal; Ayşe Nilay Evcil (Iconarp International Journal of Architecture and Planning, 2019)
Universal design is a user-focused designing approach that involves cultural, physical, mental and dimensional aspects and takes into account the needs of different personal characteristics. This study will analyze the resolutions for different personal characteristics in the design qualities of an apparel store designed by interior architecture students and then utilize the results to make suggestions for curriculum studies in which universal design embedded continuously. In terms of the different user characteristics, the study participants mainly focused on physical and visual disabilities, as well as older people and families with children. According to the participants, the most important issues to be attentive to when making interior space resolutions included reaching the shelves, disabled access ramps at the entrance, size of the circulation area, accessibility of the cashier counter, and size of the changing rooms. Another important issue related to the store design is aesthetic appeal. Serving as an indication of their concern for the commercial success of the store, the participants offered suggestions about the window display and the aesthetic quality of the store.